Market failures and the under-provision of training - Giorgio Brunello; Maria de Paola (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper reviews both the theoretical underpinnings and the empirical evidence in support of the under-provision of training. While there is little if any evidence in support of underprovision because of liquidity constraints to the demand side of the market, there is evidence that employers provide and pay for general training, and that the provision of skills encourages labor turnover. The combination of these two facts suggests that the labor market provides less training than optimal. The balance of the existing empirical evidence suggests that policy discussions should focus on the employer rather than on employees. Therefore, we conclude our review by discussing policies which affect the employer? marginal benefits and marginal costs of training.
Keywords: J24; 330; training; efficiency; turnover; Betriebliche Bildungsarbeit; Weiterbildung; Arbeitsmobilität; Marktversagen; Berufsbildungspolitik; EU-Staaten